PERLAWANAN PEREMPUAN DI PENGUNGSIAN (Studi Keberadaan Perempuan di Pengungsian Gunung Sinabung, Kabupaten Karo, Sumatera Utara) - Silfia Hanani (Kafa`ah: Journal of Gender Studies, 2014)
Women are one of the groups of people who are prone to disasterrisks. It can be seen from the situation and conditions in refugeescamp, the number of women more than the men's group. In addition,women are also experiencing problemsat the evacuation campscomplex than men, it is influenced by the condition of biological,psychological and economical faced by women.The problems facedbywomen in fact have arisingresistance among women during theevacuation, due to frequent problem among women is untouched bythe government policy. This study seeks to reveal and analyze theproblem among refugee women caused by the eruption of MountSinabung in North Sumatere. Apparently, the results showed that therewas some resistance made by women during the evacuation,amongthemis resistance to meet the needs of the issues of womanhood, suchas to get a special needs women, resistance to releasefrustration,economics. This resistance arises as a result rather than theaccommodation is not women's issues in handling disasters, and oftenforgotten problems faced by these women.  Keywords:women, resistance and evacuationCopyright © 2014 by Kafa`ah All right reservedDOI : 10.15548/jk.v4i2.94